3x - 4 x = -4

Question

Asked 8/26/2013 5:59:52 PM

Updated 8/21/2014 2:01:16 PM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [8/21/2014 2:01:16 PM]

vandar|Points 911|

eturker|Points 2985|

eturker|Points 2985|

Question

Asked 8/26/2013 5:59:52 PM

Updated 8/21/2014 2:01:16 PM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [8/21/2014 2:01:16 PM]

Rating

3

If x=-4, 3x - 4=-16.

3x - 4

=3x(-4)-4

=-12-4

=-16.

3x - 4

=3x(-4)-4

=-12-4

=-16.

Added 8/21/2014 7:12:12 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/21/2014 2:01:19 PM], Rated good by andrewpallarca

3

Evaluate the algebraic expression for the given value or values of the variable(s).If x = 2 ,6x + 2 =14.

6x + 2

=6x2+2

=12+2

=14.

6x + 2

=6x2+2

=12+2

=14.

Added 8/21/2014 7:13:04 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/21/2014 2:01:39 PM], Rated good by andrewpallarca

3x - 4;x = -4 **Weegy:** 3x - 4; x=-4:
3(-4) - 4
= -12 - 4
= -16
(More)

Question

Expert Answered

Updated 8/21/2014 2:05:20 PM

0 Answers/Comments

Solve and check the linear equation.
(-4x - 2) + 7 = -3(x + 3) **Weegy:** Please visit this site.
**User:** Simplify the algebraic expression.
-5(2x - 6) - 4x + 5 **Weegy:** 4x + 12 = -3x - 6 + 4x, 4x + 12 = x - 6, 12 + 6 = x - 4x, 18 = -3x or -3x = 18, x = -6 **User:** Write the algebraic expression without parentheses.
-(-2 + 7y) **Weegy:** -(-2 + 7y), the algebraic expression is: 2 - 7y **User:** Write the algebraic expression without parentheses.
-(4x - 9) **Weegy:** it is a special factor (a-b)(a+b) = a^2 - b^2 a=7y b=(4-4x) so the answer is 49y^2- (4-4x)^2 simplify it it will be 49y^2- 16 +32x -16x^2 rearange it , it will be 49y^2 - 16x^2 +32x-16 **User:** Write the algebraic expression without parentheses.
-(4x - 9) **Weegy:** Result is (-4 x+7 y+4) (4 x+7 y-4) **User:** Simplify the algebraic expression.
-10(8r + 9) + 9(6r + 6) **Weegy:** -10(8r + 9) + 9(6r + 6) SOLUTION: let x= answer/ simplified expression x = -10(8r + 9) + 9(6r + 6) x = -80r - 90+ 54r + 54 x = -80r + 54r - 90+ 54 x = -26r - 36 **User:** Write the algebraic expression without parentheses.
-(4x - 5) **Weegy:** Result is (-4 x+7 y+4) (4 x+7 y-4) (More)

Question

Expert Answered

Updated 6/27/2014 1:49:36 AM

6 Answers/Comments

-5(2x - 6) - 4x + 5

=(-5)(2x-6)+(-4x)+5

=(-14x)+35

=-14x+35

=(-5)(2x-6)+(-4x)+5

=(-14x)+35

=-14x+35

Added 6/27/2014 1:46:51 AM

This answer has been confirmed as correct and helpful.

The algebraic expression without parentheses : -(-2 + 7y) = -7y+2

Added 6/27/2014 1:48:12 AM

This answer has been confirmed as correct and helpful.

The algebraic expression without parentheses -(4x - 9) = -4x+9

Added 6/27/2014 1:48:46 AM

This answer has been confirmed as correct and helpful.

The algebraic expression without parentheses -(4x - 5) = -4x+5

Added 6/27/2014 1:49:36 AM

This answer has been confirmed as correct and helpful.

Write the algebraic expression without parentheses.
-(-2 + 3y)

Question

Not Answered

Updated 82 days ago|4/30/2018 3:06:09 AM

1 Answer/Comment

-(-2 + 3y) = 2 - 3y

Added 82 days ago|4/30/2018 3:06:09 AM

This answer has been confirmed as correct and helpful.

Write the algebraic expression without parentheses.
-(4x - 5) **Weegy:** Result is (-4 x+7 y+4) (4 x+7 y-4) **User:** Write the algebraic expression without parentheses.
-(-2 + 3y) (More)

Question

Not Answered

Updated 244 days ago|11/18/2017 8:57:32 PM

2 Answers/Comments

27,102,265

questions answered

There are no comments.